2000
DOI: 10.1074/jbc.m001403200
|View full text |Cite
|
Sign up to set email alerts
|

Association of l-Glutamic Acid Decarboxylase to the 70-kDa Heat Shock Protein as a Potential Anchoring Mechanism to Synaptic Vesicles

Abstract: Recently we have reported that the membrane-associated form of the ␥-aminobutyric acid-synthesizing enzyme, L-glutamate decarboxylase (MGAD), is regulated by the vesicular proton gradient (Hsu, C. C., Thomas, C., Chen, W., Davis, K. M., Foos, T., Chen, J. L., Wu, E., Floor, E., Schloss, J. V., and Wu, J. Y. (1999) J. Biol. Chem. 274, 24366 -24371). In this report, several lines of evidence are presented to indicate that L-glutamate decarboxylase (GAD) can become membrane-associated to synaptic vesicles first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…5d, lane 3). These results suggest that both HSC70 and CSP form a protein complex with GAD 65 in GABAergic SV, confirming our previous findings in synaptosomal preparation (15).…”
Section: Demonstration Of a Protein Complex Of Gad Hsc70 And Csp Onsupporting
confidence: 81%
See 3 more Smart Citations
“…5d, lane 3). These results suggest that both HSC70 and CSP form a protein complex with GAD 65 in GABAergic SV, confirming our previous findings in synaptosomal preparation (15).…”
Section: Demonstration Of a Protein Complex Of Gad Hsc70 And Csp Onsupporting
confidence: 81%
“…Hence, it is clear that two separate protein entities are responsible for synthesis and packaging of GABA into SVs. Recently, we have shown that GAD 65 may become anchored to SVs through protein complex formation first with HSC70, followed by interaction with CSP, an intrinsic SV protein (15). In this article, we have shown the presence of HSC70 and CSP in purified GABAergic SV (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This suggests that GVG does not alter GABA transport into synaptic vesicles. Future studies of this protein complex, which in addition to GAD and VGAT includes heat shock protein 70, cysteine string protein, and CaMKII (Hsu et al, 2000;Jin et al, 2003), might elucidate the relationship between GABA synthesis and transport into synaptic vesicles.…”
Section: Figurementioning
confidence: 99%